High Plasma Concentration of Factor VIIIc Is a Major Risk Factor for Venous Thromboembolism - Kraaijenhagen, Roderik A.; in 't Anker, Pieternella S.; Koopman, Marianne M. W.; Reitsma, Pieter H.; Prins, Martin H.; van den Ende, Abraham; Büller, Harry R. (Thrombosis and Haemostasis, 2000)
Established risk factors, including deficiencies of protein C, protein S or antithrombin and the factor V Leiden and prothrombin mutation, are present in about one third of unselected patients with venous thromboembolism. In addition to these inherited thrombophilic defects, elevated plasma levels of factor VIIIc have been suggested to be important in the pathogenesis of (recurrent) venous thromboembolism. The objective of this study was to assess the relevance of factor VIIIc plasma concentration in consecutive patients with venous thromboembolism.We studied the prevalence of elevated plasma levels of factor VIIIc in 65 patients with a proven single episode and in 60 matched patients with documented recurrent venous thromboembolism. The reference group consisted of 60 ageand sex-matched patients who were referred for suspected venous thromboembolism, which was refuted by objective testing and longterm clinical follow-up. To minimalize the influence of the acute phase, blood was obtained at least 6 months after the thromboembolic event and results were adjusted for fibrinogen and C-reactive protein. Factor VIIIc was re-determined several years after the first measurement in a subset of patients to evaluate the variability over time. To study a possible genetic cause, a family study was done.In the control, single and recurrent episode group, the prevalences of plasma levels of factor VIIIc above 175 IU/dl (90th percentile of controls) were 10% (95% CI: 4 to 21%), 19% (95% CI: 10 to 30%) and 33% (95% CI: 22 to 47%), respectively. For each 10 IU/dl increment of factor VIIIc, the risk for a single and recurrent episode of venous thrombosis increased by 10% (95% CI: 0.9 to 21%) and 24% (95% CI: 11 to 38%), respectively. Both low and high plasma levels of factor VIIIc were consistent over time (R = 0.80, p = 0.01). A family study indicated a high concordance for elevated factor VIIIc plasma concentrations among first degree family members. Adjustment for fibrinogen, C-reactive protein and known thrombophilic risk factors did not change the observed association of elevated factor VIIIc with thrombosis.Elevated plasma levels of factor VIIIc are a significant, prevalent, independent and dose-dependent risk factor for venous thromboembolism. It also predisposes to recurrent venous thromboembolism.
Keywords: Thromboembolism; factor VIII; venous thrombosis; risk factor